Clinical Evaluation of Significance of 25(Oh)D (Vitamin D) Status in Swine Flu (H1N1) - Bal, Kishan Gupta; Kashish, Narula; Makhan, Lal Saini; Rakesh, Kumar Baberwal; Jigyasa, Gupta; Sunil, Rulaniya (International Journal of Nutrition, 2020)
Background Since swine flu has been declared pandemic in 2009 it has become a major challenging public-health problem associated with high morbidity and mortality. 25(OH)D deficiency is also pandemic and has been reported to be clinically correlated with decreased immunity and respiratory infections. The possible role of vitamin D in infections is implied from its impact on the innate and adaptive immune responses. This study is planned to evaluate clinical significance of 25(OH)D status on course and outcome in hospitalized cases of swine flu and to compare it with normal healthy subjects living in the same vicinity to evaluate if vitamin D is having any protective effect. Material & Methods Present prospective cross-sectional study was conducted on 79 RT-PCR confirmed cases of swine flu admitted during recent epidemic. All patients were evaluated thoroughly by clinical history physical examination and laboratory investigations as per Performa and followed-up during hospital stay. 25-hydroxyvitamin D (25(OH)D) estimation was done by electro-chemiluminescent Assay in all the cases and it was also done in 36 normal healthy family members of study patients living in the same vicinity (control group). Results High prevalence (70.9%) of low (≤30ng/ml) status of 25(OH)D was observed in cases of swine flu as compared to control group. 25(OH)D status was associated with severity of illness. Mean value of 25(OH)D in mechanically ventilated patients was 9.81±6.43 while it was 22.76±11.35 ng/ml in patients who do not required ventilation (p<0.05). Mean 25(OH)D level in patients who stayed in hospital for <5 days was 28.60±8.79 ng/ml, 24.18±11.67 for 6-10 days and 8.23±2.12 for >10 days (p<0.01). Mean value of 25(OH)D in patients who died was 9.59±5.90 ng/ml as compared to 23.13±11.62 ng/ml who survived (p<0.01). Conclusion Our study suggests that 25(OH)D may have preventive role for swine flu infection. Low level of 25(OH)D is associated with high morbidity in terms of increase requirement for mechanical ventilation, multiorgan dysfunction and long duration of hospital stay. 25(OH)D deficiency is associated with high mortality in swine flu. 25(OH)D status should be given due consideration in high risk patients especially during winter season.
Keywords: Swine Flu; 25(OH)D; vitamin D; Multiorgan; Mechanical Ventilation